Efficacy and safety of VT ablation of electrical storm. (19th May 2022) - Mueller, J; Nentwich, K; Berkovitz, A; Halbfass, P; Ene, E; Sonne, K; Simu, GR; Chakarov, I; Deneke, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Data about VT ablation in patients with electrical storm (ES) is limited. This study sought to compare the prognostic outcome of patients with ES to those with ventricular tachyarrhythmias but without ES undergoing VT ablation on mortality, VT recurrence rates, rehospitalization rates and major adverse cardiac events (MACE). Methods: In this large single-centre study patients presenting with ES and undergoing VT ablation from June 2018 to April 2021 were compared to patients undergoing VT ablation due to ventricular tachyarrhythmias but without ES. The primary prognostic outcome was cardiovascular mortality, secondary endpoints were VT recurrence rates, rehospitalization rates and MACE all after a median follow-up of 22 months. Results: A total of 311 patients underwent a first VT ablation due to ventricular tachyarrhythmias and were included (63 ± 14 years; 86% male). Of them 108 presented with ES. In the ES cohort dilated cardiomyopathy as underlying heart disease was significantly increased (p=0.008), whereas all other cardiomyopathies were equally distributed. Major complications were equal among both groups (p>0.05). Ablation of the clinical VT was achieved in 95% of all patients without ES and in 94% of all patients with ES (p>0.05). Noninducibility of any VT was achieved in 91% without ES and in 76% with ES (p=0.001). This was also reflected in higher VT induction rates in non-invasive programmed stimulation before hospital discharge among ES patients (40% vs. 19%; p=0.031). After a median of 22 months of follow-up, patients with ES revealed slightly increased cardiovascular mortality rates (17% vs. 9%; log-rank p=0.061; HR 1.902; CI 95% 0.961 – 3.765; p=0.061). Furthermore, ES patients suffered from increased VT recurrence rates (59% vs. 40%; log rank p=0.006), rehospitalization rates (73% vs. 49%; log rank p=0.001) and MACE (71% vs. 45%; log rank p=0.001). ES patients displayed a 1.7-fold increased risk for VT recurrence (HR 1.701; CI 95% 1.160 – 2.493; p=0.006), a 1.9-fold increase for rehospitalization (HR 1.885; CI 95% 1.366 – 2.600; p=0.001) and a 1.9-fold increase for occurrence of MACE (HR 1.935; CI 95% 1.398 – 2.679; p=0.001). Presence of ES was the only independent predictors of VT recurrence and occurrence of MACE, whereas ES and decreased LVEF were independent predictors of rehospitalization. Conclusions: VT ablation in patients with ES is challenging and these patients reveal highest risk for recurrent VTs, rehospitalization and MACE. These patients need close follow-ups and optimal guideline-directed therapy.